A DISTINCTIVE PENTECOSTAL HERMENEUTIC: POSSIBLE AND/OR NECESSARY? - Nel, Marius (Acta Theologica, 2017)
Over the past twenty years, Pentecostal theologians have published extensively on hermeneutical issues, a subject that had not received much consideration before the mid-1990s. In their discussion of hermeneutical issues, Pentecostal theologians may create the impression that their hermeneutics is so unique that one can speak of a distinctive Pentecostal hermeneutics. This article raises the question as to whether it is possible and/or necessary to speak of such a distinctive hermeneutics. The growing debate among Pentecostals about hermeneutical issues demonstrates that they disagree on several important issues. They should also discount the difference between an academic hermeneutics and what happens on their pulpits and in their pews. Although there are specific identifiable emphases in a Pentecostal hermeneutics, it does not qualify to be called distinctive, and an ecumenical approach demands that the movement should function within the context of the wider Christian church and its history of reading and interpreting the Bible.